INTERNET CSR PRESENTATION AND ITS IMPORTANCE FOR INCREASING CORPORATE REPUTATION IN THE AREA OF FERROUS METALLURGY - Jelínková, Martina; Munzarová, Simona; Lošťáková, Hana (TANGER, spol. s r.o., 2016)
Within CSR (corporate social responsibility), one of the key areas is certainly its communication towards all the involved parties (stakeholders). CSR communication can then be used as an effective marketing tool increasing, in the eyes of the business partners, the company’s prestige and contributes to its positive reputation. In spite of that, it is still possible to see on the market that a lot of companies underestimate the importance of presentation of CSR of their own company, and that they either do not pay sufficient attention to it, or that they, by contrast, exaggerate their activities within CSR. Although a legislative framework in the area of CSR reporting on the national level is not expected until 2017, companies should already be paying proper attention to presentation of their CSR now. And the internet is naturally becoming the basic platform for presentation of corporate activities in all areas, i.e. also in the area of CSR. The paper summarizes the outcomes of a primary survey conducted by University Pardubice, which evaluates the current internet presentation of CSR in the area of ferrous metallurgy and describes the importance of the given web presentation for increasing the corporate prestige in the eyes of the stakeholders, as perceived by companies. In conclusion, the paper summarizes the most frequent mistakes and presents ideas how to improve internet communication of CSR in the area of ferrous metallurgy.
Internetová prezentace CSR a její význam pro zvyšování reputace firem v oblasti hutnictví železa
Keywords: CSR; CSR Communication; Corporate Reputation; Ferrous Metallurgy; Společenská odpovědnost firem; komunikace společensky odpovědných aktivit firmy; reputace podniku; hutnictví železa